A Adaptation Analysis of Education and Training Information System Acceptance with Technology Acceptance Model Approach - Putu Vierda Lya Suandari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The Covid-19 pandemic has had a significant impact on various aspects of human life. All aspects start from changes in the way manual work towards digitalization, one of which is the application of information systems that support human resources in hospitals in following these changes. Acceptance of implementing new information systems such as the Online Education and Training Information System in hospitals that do not meet user expectations can cause system user discomfort which has an impact on hospital employee performance. To anticipate this, it is necessary to understand the basic factors that contribute to acceptance in the implementation of online education and training information systems using the Technology Acceptance Model (TAM) approach. This study aims to describe the evaluation of the acceptance of the online education and training information system using the TAM model approach at General Hospital X Denpasar. The analysis used in this study uses Partial Least Square (PLS) with a total of 99 respondents using the measured system. The results of the evaluation of the TAM model show that the acceptance of the online education and training information system has a positive assessment seen from the attitude of the user in responding to the acceptance of new technology.